Pengaruh Kedisiplinan Siswa dan Minat Belajar Terhadap Hasil Belajar Pada Mata Pelajaran Dasar-Dasar Manajemen Perkantoran dan Layanan Bisnis di SMKN 48 Jakarta - Erika Dosista; Christian Wirarendi Wolor; Darma Rika Swaramarinda (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
This study aims to examine the effect of student discipline and learning interest on learning outcomes in basic office management and business services subjects at SMK Negeri 48 Jakarta. The study used a quantitative approach with a correlational method. Data was collected from 54 students using a questionnaire that measured their level of discipline, interest in learning, and learning outcomes. The results of the analysis show that learning interest has a positive and significant influence on learning outcomes, with a coefficient value of 0.585 (p < 0.001). Meanwhile, student discipline has a positive but insignificant influence on learning outcomes (coefficient 0.196, p = 0.104). Overall, discipline and interest in learning together have a significant influence on student learning outcomes (F = 24.564, p < 0.001). This finding suggests that interest in learning is the main factor in improving learning outcomes, while discipline, although important, does not directly affect learning outcomes significantly.